2012
DOI: 10.1002/pi.4358
|View full text |Cite
|
Sign up to set email alerts
|

Novel polyarylates containing aryl ether units: synthesis, characterization and properties

Abstract: To improve the processability of the poly(p‐hydroxybenzoic acid), copolyarylates containing m‐aryl ether units were synthesized using p‐acetoxybenzoic acid, 1,4‐diacetoxybenzene and 1,3‐bis(4'‐carboxyphenoxy)benzene by melt transesterification reaction. The structure and properties of these polyarylates were characterized using infrared spectra, differential scanning calorimetry, thermogravimetric analyses, wide‐angle X‐ray diffraction and polarized optical microscopy etc. The results showed that all polyaryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…HQ, m ‐dihydroxybenzene, potassium carbonate, N ‐methyl‐2‐pyrrolidone (NMP), 4‐hydroxybenzoic acid, toluene, ethanol, acetic anhydride, sulfuric acid, p ‐hydroxybenzoic acid (PHBA), zinc acetate, diantimony trioxide, dimethyl sulfoxide (DMSO) (all from Chengdu Ke Long Co.), and 4,4′‐difluorobenzophenone (DFBP, from Wuhan XinHuayuan chemical Co.) were analytically pure and used as received. 1,3‐bis(4′‐carboxylphenoxy)benzene [PMP(COOH) 2 ] was prepared in our laboratory and the synthesis route was reported by our previous work 20…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HQ, m ‐dihydroxybenzene, potassium carbonate, N ‐methyl‐2‐pyrrolidone (NMP), 4‐hydroxybenzoic acid, toluene, ethanol, acetic anhydride, sulfuric acid, p ‐hydroxybenzoic acid (PHBA), zinc acetate, diantimony trioxide, dimethyl sulfoxide (DMSO) (all from Chengdu Ke Long Co.), and 4,4′‐difluorobenzophenone (DFBP, from Wuhan XinHuayuan chemical Co.) were analytically pure and used as received. 1,3‐bis(4′‐carboxylphenoxy)benzene [PMP(COOH) 2 ] was prepared in our laboratory and the synthesis route was reported by our previous work 20…”
Section: Methodsmentioning
confidence: 99%
“…In our previous work,20 in order to reduce the melting temperature of TLCP with reserving thermotropic liquid crystalline state, a series of liquid crystalline copolyarylates containing m ‐aryl ether units were synthesized using p ‐acetoxybenzoic acid (PABA), 1,4‐diacetoxybenzebe (DAB), and 1,3‐bis(4′‐carboxyphenoxy)benzene [PMP(COOH) 2 ] by melt transesterification reaction. We considered blending those liquid crystalline copolyarylates with poly(ether ether ketone) (PEEK) to reduce the melt viscosity and improve the processability of PEEK.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the addition of TLCP significantly reduced the melting viscosity of PEEK, especially at a shear rate of 118 s −1 ; the mechanical properties were improved when the content of TLCP exceeded 10 wt %. In previous works of our group, we synthesized a thermotropic liquid crystalline polyarylate (PEAR) and applied it in facilitating the processibility of PEEK and polyphenylene sulfide . However, both Vectra 950A and PEAR were incompatible or semicompatible with PEEK; as a result, the composites could not achieve the best mechanical properties as we expected.…”
Section: Introductionmentioning
confidence: 94%
“…In previous works of our group, we synthesized a thermotropic liquid crystalline polyarylate (PEAR) and applied it in facilitating the processibility of PEEK and polyphenylene sulfide. [18][19][20] However, both Vectra 950A and PEAR were incompatible or semicompatible with PEEK; as a result, the composites could not achieve the best mechanical properties as we expected. It is worthwhile to find a kind of TLCP that is compatible with PEEK to improve the processibility and mechanical properties of PEEK simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…This is because Vectra has poor compatibility with PEEK. Our previous works have reported two modification strategies to modify TLCPs for improving the compatibility between PEEK and TLCP . However, the synthesized TLCPs and PEEK are just partially compatible, so they are not highly effective processing agent for PEEK.…”
Section: Introductionmentioning
confidence: 99%